1990
DOI: 10.1111/j.1432-1033.1990.tb19254.x
|View full text |Cite
|
Sign up to set email alerts
|

The bovine plasma retinol‐binding protein

Abstract: 1. The primary structure of bovine plasma retinol-binding protein (RBP) has been determined and found to be more than 90% identica1 to human and rabbit RBPs, and more than 80% identical to rat RBP. Main changes in amino acid sequence are observed in two regions on the surface of the protein molecule (residues 138 -148 and 2. The interactions of bovine RBP with bovine and human transthyretins were investigated using the technique of fluorescence polarization. Bovine RBP was able to form high affinity complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
2
23
2
Order By: Relevance
“…The high degree of cross-interaction between RBP and transthyretin isolated from evolutionarily distant vertebrate species has been explained by the existence of a particularly conserved site in the RBP molecule which participates in the protein-protein recognition [7,91. Some regions appear especially conserved in mammalian RBPs [6, 71.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The high degree of cross-interaction between RBP and transthyretin isolated from evolutionarily distant vertebrate species has been explained by the existence of a particularly conserved site in the RBP molecule which participates in the protein-protein recognition [7,91. Some regions appear especially conserved in mammalian RBPs [6, 71.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the primary structures of mammalian RBPs are approximately 90% identical [5 -71, the similarity between the primary structures of Xenopus laevis RBP, whose amino acid sequence has been deduced from its cDNA sequence [8], and human RBP is significantly reduced to 63%. Fluorescence polarization studies have shown that human RBP and transthyretin cross-interact with the bovine or chicken counterparts with high affinity [7,91; therefore, highly conserved regions on the two proteins participate in the protein -protein recognition. It has also been reported that the retinol-containing proteins in amphibian and reptilian plasma exhibit an apparent molecular mass of 60 -80 kDa (i.e.…”
Section: _ _ _ _mentioning
confidence: 99%
See 3 more Smart Citations